HUBUNGAN LAMA HEMODIALISA DENGAN STATUS NUTRISI PADA PASIEN GAGAL GINJAL KRONIK DI RUANG HEMODIALISA - Dewi Ratnasari (Jurnal Skolastik Keperawatan, 2020)
Introduction: Chronic Kidney Disease is a deterioration of kidney function that occurs for 3 months or more. Gastrointestinal disorders such as nausea, vomiting, and loss of appetite can change their nutritional status. Nutritional status assessment is a major component in evaluating and managing patients. Purpose: This research aimed to discover the correlation of the duration of hemodialysis and the nutritional status of patients with Chronic Kidney Disease. Method : This was a quantitative research with an analytic observational design and a cross-sectional approach. The test used in this study was the Chi-Square test. Sample using an accidental sampling method. Results: This study obtained the highest value on normal nutritional status with HD duration > 12 months, this was caused the person who has undergone hemodialysis for long duration has become accustomed to gastrointestinal disorders, such as nausea, vomiting, and diarrhea. The longer duration for people undergo hemodialysis, the more hemodialysis provides opportunities for patients to be more adaptive to the therapeutic program that they are undergoing. Conclusion: P-value 0,221 (p>0,05). It means that there was no significant correlation between the duration of hemodialysis and patients' nutritional status. Keywords: Chronic Kidney Disease, duration of hemodialysis, nutritional status